Continent-wide distribution in mycorrhizal fungi: Implications for the biogeography of specialized orchids - Davis, B.; Phillips, R.; Wright, M.; Linde, C.; Dixon, Kingsley (Oxford University Press, 2015)
Background and Aims: Although mycorrhizal associations are predominantly generalist, specialized mycorrhizal interactions have repeatedly evolved in Orchidaceae, suggesting a potential role in limiting the geographical range of orchid species. In particular, the Australian orchid flora is characterized by high mycorrhizal specialization and short-range endemism. This study investigates the mycorrhizae used by Pheladenia deformis, one of the few orchid species to occur across the Australian continent. Specifically, it examines whether P. deformis is widely distributed through using multiple fungi or a single widespread fungus, and if the fungi used by Australian orchids are widespread at the continental scale. Methods: Mycorrhizal fungi were isolated from P. deformis populations in eastern and Western Australia. Germination trials using seed from Western Australian populations were conducted to test if these fungi supported germination, regardless of the region in which they occurred. A phylogenetic analysis was undertaken using isolates from P. deformis and other Australian orchids that use the genus Sebacina to test for the occurrence of operational taxonomic units (OTUs) in eastern and Western Australia.Key Results: With the exception of one isolate, all fungi used by P. deformis belonged to a single fungal OTU of Sebacina. Fungal isolates from eastern and Western Australia supported germination of P. deformis. A phylogenetic analysis of Australian Sebacina revealed that all of the OTUs that had been well sampled occurred on both sides of the continent. Conclusions: The use of a widespread fungal OTU in P. deformis enables a broad distribution despite high mycorrhizal specificity. The Sebacina OTUs that are used by a range of Australian orchids occur on both sides of the continent, demonstrating that the short-range endemism prevalent in the orchids is not driven by fungal species with narrow distributions. Alternatively, a combination of specific edaphic requirements and a high incidence of pollination by sexual deception may explain biogeographic patterns in southern Australian orchids.